Reflections: the Story of the Exhibition
VHS. Reflections The Story of the Exhibition, The Treasure Houses of Britain focuses on the behind- the scences story of the creation and exhibitions the National Gallery of Art has undertaken. Whith J. Carter Brown as guide, the program takes the viewer througth th exhibitionïs 17 rooms while hilghlighting key themes and exploring the showïs history, planning, and desing. Commentary by the curator and designer, together with unusual documentary installation footage, provide rare insight into the making of an exhibition